ENHANCING STUDENTS’ SPEAKING SKILL THROUGH DIGITAL STORYTELLING - Eka Puteri Elyani; Yusuf Al Arief; Rizky Amelia; Inayati Fitriyah Asrimawati (Universitas Lambung Mangkurat, 2022)
Abstract: Speaking is an important productive skill and students need to master this skill. However, some students are still not accustomed to speak English because of some factors, one of them is the lack of using some media that can help to speak English in the classroom. Some teachers tend to explain the materials directly then do the exercises without any media involved. Media could be the solution in students’ speaking skill. The use of media in the classroom are hoped to give the contribution to students in developing different learning styles and making the process of learning more interesting and enjoyable. Telling story digitally comes as the new frame of telling story to replace telling story traditionally. Through the use of multimedia technology, digital storytelling is a form of telling story that enables students to write their own stories using their own words and record their voices or videos based on the digital images they have. This research employs experimental study on the effectiveness of digital storytelling to teach speaking. The samples were experimental class which treated using digital storytelling and control class which treated using picture-cued storytelling. ANOVA with multifactor analysis was used to analyses the data. This study’s findings show that digital storytelling enhances students’ speaking abilities more than picture-cued storytelling.